BUREAUCRACY REFORM IN TAX SERVICES ONLINE IN THE KUPANG CITY - Adam, Cataryn Vlantyna; Seran, Sirilus; Kerihi, Anthon Simon Yohanis; Libing, Zet Sony (Natapraja, 2023)
This study examined the factors behind the advancement of bureaucratic reform in online tax services at the Regional Technical Service Unit (RTSU) of Regional Income for the City of Kupang, or Unit Pelaksana Teknis Daerah (UPTD). This investigation employed a qualitative method with an interpretive paradigm. This analysis discovered five factors from the internal and external dimensions of the bureaucracy that affect the quality of online tax revenue. From internal sources, this article found that the lack of leadership commitment, the weak capacity and professionalism of implementing actors, and the lack of budget allocations contributed to the weak progress of bureaucratic reform in online tax services. Meanwhile, on the external dimension, this study uncovered that the lack of public pressure and the existence of business practices in the service process contributed to strengthening the low quality of online tax services. To increase the quality of online tax services, the government must ensure that the public managers appointed firmly commit to the bureaucratic reform agenda. Additionally, the government needs to increase front-line implementers' professionalism and capacity to learn information technology. Finally, the government needs to minimize the occurrence of business practices in the process of public services.